Relationship between training effectiveness, motivation and public hospitals food handlers’ food safety practice / Norhafizah Omar and Aslinda Mohd Shahril - Omar, Norhafizah; Mohd Shahril, Aslinda (Universiti Teknologo MARA Selangor, 2019)
This study aims to examine the relationship between training and employee food safety practice and to examine whether motivation mediates the relationship between training effectiveness and employee food safety practice. This quantitative study was conducted using questionnaires and the unit of analysis was Selangor public hospitals food handlers. The regression analysis confirms a significant relationship between training attributes and food safety practice, training attributes and motivation, and motivation significantly affect food safety practice. Lastly, the mediation analysis confirms that motivation mediated the relationship between training and food safety training. The program design and training evaluation of the food safety training would enhance the food safety practice among the public hospitals' food handlers.